2015
DOI: 10.1186/s13673-015-0053-y
|View full text |Cite
|
Sign up to set email alerts
|

How does this message make you feel? A study of user perspectives on software update/warning message design

Abstract: Software update messages are commonly used to inform users about software updates, recent bug fixes, and various system vulnerabilities, and to suggest recommended actions (e.g., updating software). While various design features (e.g., update options, message layout, update message presentation) of these messages can influence the actions taken by users, no prior study can be found that investigated users opinions regarding various design alternatives. To address this void, this paper focuses on identifying so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 20 publications
3
12
0
Order By: Relevance
“…Das et al showed that social influences were key in users' consideration of security decisions and impactful towards security outcomes [20]. Several studies have identified the importance of individual considerations in the decision of users to apply a software update [21][22][23][24]. In particular, past experiences were identified to be an important factor in users' decisions, particularly if past experiences were negative [22,23].…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Das et al showed that social influences were key in users' consideration of security decisions and impactful towards security outcomes [20]. Several studies have identified the importance of individual considerations in the decision of users to apply a software update [21][22][23][24]. In particular, past experiences were identified to be an important factor in users' decisions, particularly if past experiences were negative [22,23].…”
Section: Related Workmentioning
confidence: 99%
“…Several studies have identified the importance of individual considerations in the decision of users to apply a software update [21][22][23][24]. In particular, past experiences were identified to be an important factor in users' decisions, particularly if past experiences were negative [22,23]. In addition to user perceptions, more work in cybersecurity is also taking a more explicitly psychological approach towards understanding users' computer security behaviors, as shown in Howe et al 's 2012 survey of literature related to the psychology of end-users [25].…”
Section: Related Workmentioning
confidence: 99%
“…It has been widely established that changes to features and interfaces are common reasons for not updating, especially after previous negative experiences [5], [13], [23]- [26]. Bergan and Whittaker [23] explained the impact of changes to interfaces in terms of five key cognitive concepts: a loss of cognitive automation (a need for more attention to the task after a user interface is made less familiar); negative transfer effects (the need to discard skills learned 'doing things the old way'); the need to rebuild cognitive maps (such as rediscovering where a menu item is); the need to retrain procedural memory ('even if we know 'in our heads', our 'hands' still do what they used to do with the old interface') and; the demotivating effects on the user of a feeling of loss of overall control.…”
Section: B the Need For Human Controlmentioning
confidence: 99%
“…Many previous studies about software updating e.g. [7], [22], [26] have also drawn participants from academically biased pools. These participants might be more technically savvy, with more technically accurate mental models of updates.…”
Section: Survey Studymentioning
confidence: 99%
“…Step 1: WAP ⟶ S: = { , , , , } The firmware upgrade is started when the WAP administrator performs a firmware upgrade or a regularly scheduled application is started [27]. The WAP sends a client hello message to the server S. The client hello contains the TLS version, a random number of 32 bytes, the session ID, and the supported encryption and compression algorithms.…”
Section: Proposed Firmware Upgrade Protocolmentioning
confidence: 99%